2023
DOI: 10.1111/1365-2664.14439
|View full text |Cite
|
Sign up to set email alerts
|

A framework to apply trait‐based ecological restoration at large scales

Abstract: Upscaling trait‐based restoration to regional levels is necessary as we enter the UN Decade on Ecosystem Restoration. For this, we need to select species that achieve functional targets considering the regional species pool. Here, we present a framework to achieve multiple restoration targets using a regional species pool containing the species available on the market, species unavailable, and species that occur in reference ecosystems. The framework enables optimising functional diversity (FD), recovering FD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
2
1
Order By: Relevance
“…Despite wide interest in the development of a plant trait-based approach to restoration (e.g. Carlucci et al, 2020;Coutinho et al, 2023;Laughlin, 2014), we found little consistency in responses among species with shared traits. We invite future research of species responses to disturbances in ecological restoration to inform vegetation development.…”
Section: Other Potential Drivers Of Resprouting Successcontrasting
confidence: 74%
“…Despite wide interest in the development of a plant trait-based approach to restoration (e.g. Carlucci et al, 2020;Coutinho et al, 2023;Laughlin, 2014), we found little consistency in responses among species with shared traits. We invite future research of species responses to disturbances in ecological restoration to inform vegetation development.…”
Section: Other Potential Drivers Of Resprouting Successcontrasting
confidence: 74%
“…S‐SDMs can offer practitioners lists of species that will persist over time in a given area, thus boosting climate change resilience in restoration projects (Butterfield et al., 2017; Fremout et al., 2020). The species selection for restoration can be further refined by crossing S‐SDM recommendations with the species available on the market as seeds and seedlings (Coutinho et al., 2023; Silva et al., 2022). We have made available an R script based on the analyses presented here for (1) conservationists to visualize the current and future distribution of all the 7398 species studied here, and (2) restoration practitioners to generate lists of species prone to occur in a specified coordinate in the future (2040).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating TGB functioning into restoration practice is imperative for enhancing ecosystem resilience (Coutinho et al., 2023). Despite TGB having evolved with endogenous disturbances and specific edaphic conditions (Buisson et al., 2019; Veldman et al., 2015), only 55% of the experiments manipulated fire, herbivores or soils, and only 5% simultaneously manipulate two drivers.…”
Section: Discussionmentioning
confidence: 99%